Risk Factors of Multidrug-Resistant Tuberculosis - Paudel, Sita (International Journal of Applied Sciences and Biotechnology, 2017)
Multidrug-resistant tuberculosis has been increased worldwide which is a severe problem. A case-control study was carried out among 50 MDR-TB cases and 63 drug susceptible controls to identify risk factors associated with multidrug-resistant tuberculosis (MDR-TB) in Lumbini Zone. Irregularity in taking medicine (OR=2.36), large family size (OR=2.40), farming as occupation (OR=2.83), history of TB and bovine at home (OR=6.5) were statistically associated with MDR-TB. Most of the MDR-TB cases were males (82%) and individual with the age group 21-30 years (40%) were highly infected with MDR-TB Int. J. Appl. Sci. Biotechnol. Vol 5(4): 548-554